HOUSE LAYOUT TYPOLOGY STUDY IN SLUM AREA Case Study : Kampung Jawa, Denpasar, Bali - Prabawa, Made Suryanatha (Journal of Architectural Research and Education, 2020)
Kampung Jawa is a settlement located in the heart of Denpasar, the capital city of Denpasar. These Settlement actual name was Dusun Wanasari, but people of Denpasar usually call it â€œKampung Jawaâ€. Kampung Jawa historical background can be traced back to year 1907, when many Javanese merchant came to bali to trade. These Javanese merchant later on given a land to buil their settlement by the Kingdom Badung. From 1907 until today (2020) Kampung Jawa have grown today 10.250 people live there. Slums area, is what the government of Denpasar terminology for Kampung Jawa because it is a highly dense populated area (10.250 people in 8.945 m2 settlement area). This research depart from the issue of Kampung Jawa as a slums area becoming a Government problems, but it must be having a unique characteristics, especially for their House Layout. This research conducted using exploratory and qualitatives methods. Exploratory for findings house typology and qualitative for digging reasons behind the typology and residentâ€™s conditions in Kampung Jawa. Results dan findings shows that residentâ€™s of Kampung Jawa lack of education, so they lack of â€œLaborâ€ aspect that then affected their â€œWorkâ€ and â€œActionâ€ aspects. Because of lack of â€œLaborâ€ residents of Kampung Jawa didnâ€™t get to know about better living, they just live with an efficient way as long as they can survive to live in Denpasar. These thought brought themn to create an efficient Â land use and as a results a mixed function house layout typology. From the finding, this research can conclude that Kampung Jawaâ€™s Residents way of living was unique and can be said that they adapt to their condition and creat a Compact House according to their own criteria-mostly their occupation.